PEMERIKSAAN MUTU KARET RSS MENGGUNAKAN PENGOLAHAN CITRA - Usman Ahmad; Fahmi Riadi; I Dewa Made Subrata (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT Evaluation of ribbed smoked sheet (RSS) quality is commonly done manually through an assessment of rubber sheet surface appearance based on its unifromity and brightness of color, and also existence of physical defect like air bulb, with spot and spotted by fungus prior to classification into RSS-1, RSS-2 and of RSS-3. This reseacrh aimed to develop a method to evaluate RSS quality using image processing. Each 40 sheets of simple in a size of 30x25 cm was capture using a CCD camera from 40 cm distance with a resultion 341x256 Pixels. The characteristics observed were RBG index, HSI color components, and textural features. Three goups of sample could be discriminated using blue color index with 80.0%, 82.5% forRSS-1, 60.0% for RSS-2 and 97.5%, ForRSS-3. Grading based on HSI color modelgave better result with 86%, 77.5%, 85.0% and 95.0% accuracy for the RSS-1, RSS-1 and RSS-3, respectively. The computer-based grading indicated that the classification by computer using HSI component was more reliabe than manually grading.In conclusion, the developed algorithm was able to classify 120 samples and corrected some of miss-classification by manual grading. Keyword: image processing, ribbed smoked sheet, grading